Relationship between biomechanical parameters technique of the preliminary rotations among elite woman hammer throwers - Rozhkov, V.; Pavlenko, V.; Pavlenko, Y.; Pavlenko, T.; Shutieieva, T.; Shutieiev, V. (Slobozhanskyi herald of science and sport, 2021)
Purpose: to determine the relationships technique of the first preliminary rotation of the hammer with technique of the second preliminary rotation of elite women`s hummer throwers.